Report of Experts' Committee on Educational Expenditure - Planning Commission (Planning Commission, 1999)
At present the proportion of the national income devoted to education in India is small in comparison with that in advanced countries of the world. If we have to move forward in this competitive age and face the challenges of globalisation and market economy, then investment in human resource development is imperative. In order to assess the present position of expenditure on education and devise a strategy for increase of spending on education, both at the Centre and in the States, the Planning Commission had set up an Expert Committee. The Expert Committee after careful analysis has strongly recommended that six per cent of the Gross Domestic Product be spent on Education in the Public Sector. The ideal situation is to implement this recommendation immediately. However, if Government is constrained by financial considerations, it should reach this target latest by the year 2007. Further, the Committee has recommended concrete measures how we could generate the financial resources required to realise the desired goal.
Education Division, Planning Commission, Yojana Bhavan, New Delhi-110 001.